National Income Towards Equity Though Green Economy (Gini Comparative Analysis of Urban and Rural Ratios) - Firman Syah, Ardy (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2022)
The start of national financial development gives the government a centre on taking care of the economy similarly in both country and urban regions. In developing countries, there are many problems that are often found, one of which is inequality in the distribution of income with rural and urban income for each person. The approach utilized in this inquiry is subjective with a descriptive analysis. The examination method utilized could be a writing look and case examination related to the substance of breaking even with the dissemination of national wage calculate the Gini ratio for each region and then involves calculating the amount required to calculate the Gini coefficient, which involves the cumulative proportion of the population and the proportion of income received by that group and the green economy concept. This consideration demonstrates seven vital steps in a green economy utilizing macro-regional financial markers, specifically veritable to observing national wage dissemination. This result depicts concepts of green economy, green development, and green development, essentially planning to operationalize the linkages of financial, social, and natural columns within feasible advancement.  Keywords: economic growth, green economy, Urban and rural ratio, Gini ratio JEL Classification: E22, O15